Muslim perspectives on palliative care in perinatal and neonatal patients: a mini-review - Shoaib, Abdullah B.; Vawter-Lee, Marissa; Venkatesan, Charu; Soliman, Ayman F. (Frontiers in Pediatrics, 2023)
Muslims comprise nearly a quarter of the worldwide population, with significant populations in the United States, Canada, and Europe. As clinicians, it is important to be familiar with Islamic religious and cultural perspectives on medical treatment, life-prolonging measures and comfort and palliative care, but historically, this has been a gap in the literature. Recently, there have been multiple papers discussing Islamic bioethics, particularly in regards to end of life care in adults; however, there has been a lack of literature discussing the Islamic perspective on issues related to neonatal and perinatal end of life care. This paper uses clinical scenarios to review key relevant principles of Islamic law, discussing the primary and secondary sources used in formulating fatawa, including the Quran, hadith, qiyas, and ‘urf, and the importance of preservation of life and upholding of human dignity (karamah). Neonatal and perinatal scenarios are used to specifically explore the Islamic perspective on withholding and withdrawal of life-sustaining measures and determining what constitutes an acceptable quality of life. In some Islamic cultures the expertise of the patient’s physician is given significant weight in making these judgments, and as such, families may appreciate frank assessment of the situation by the clinical team. Because of the various factors involved in issuing religious ruling, or fatwa, there is a wide spectrum of opinions on these rulings, and physicians should be aware of these differences, seek counsel and guidance from local Islamic leaders, and support families in their decision-making process.